2023
DOI: 10.1099/acmi.0.000490.v4
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol extraction: a comparison of methodologies

Abstract: Ergosterol is a component of the cell membrane of mycorrhizal fungi and is frequently used to quantify their biomass. Arbuscular mycorrhizal (AM) fungi and ectomycorrhizal (ECM) fungi establish a symbiotic relationship with a respective host plant. Several methods are currently employed for quantification of ergosterol; however, these utilise a series of potentially hazardous chemicals with varying exposure times to the user. The present comparative study aims to ascertain the most reliable method to extract e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[ 41 ], does not allow for sufficient arbuscular quantification. As also described by Wilkes [ 31 ], employment of potassium hydroxide during root staining has the potential to damage root cortical arbuscules, further reducing their quantification. Increases in quantified root arbuscules and fungal biomass in compost-amended soils of the present study were also reported by Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ], does not allow for sufficient arbuscular quantification. As also described by Wilkes [ 31 ], employment of potassium hydroxide during root staining has the potential to damage root cortical arbuscules, further reducing their quantification. Increases in quantified root arbuscules and fungal biomass in compost-amended soils of the present study were also reported by Yang et al .…”
Section: Discussionmentioning
confidence: 99%